Human anatomy & physiology - Marieb, Elaine Nicpon, 1936-2018; Hoehn, Katja (Harlow : Pearson, 2023)
'Equip your students with the 21st-century knowledge in A&P and encourage them to think like future scientists in the field. Human Anatomy & Physiology,12th edition will support your students' learning step-by-step, with a range of visual features, figures, and engaging writing style, alongside powerful interactive material with Mastering A&P.'--
Includes bibliographical references and index.
'EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA.' Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Online resource; title from PDF title page (EBSCO, viewed February 20, 2024).
WorldCat record variable field(s) change: 050, 082, 650
Keywords: Human physiology; Human anatomy; Anatomy; anatomy